The agency of rural women against violence: The case of the Unalahua-Salcedo community - Tello Carrillo, Jessenia (Nomadías, 2022)
This essay analyzes the agency of women confronting gender violence in the Unalahua community located in Salcedo-Ecuador. Violence is perpetrated mainly by women’s partners in domestic spaces. Based on a set of interviews and field observations, this text analyzes the tools that women have used to respond to this violence. Phenomena such as gender violence, high rates of poverty in rural areas, silence as a strategy to mitigate violence, “strike back”, and clandestine networks of support and containment, contribute to the thinking of other forms of agency in the face of violence in rural areas. Given this scenario, women proved to be “active agents” in the construction of a different reality based on their own experiences.